Eleven new species of Sericostomatoidea from Madagascar (Trichoptera: Helicopsychidae, Petrothrincidae, Sericostomatidae) - Johanson, Kjell Arne; Oláh, János (Zootaxa, 2006)
Eleven new Trichoptera species of the superfamily Sericostomatoidea are described from Madagascar. Three species within Helicopsychidae are described as Helicopsyche (Petrotrichia) ambodiva, new species, Helicopsyche (Petrotrichia) sahadika, new species, and Helicopsyche (Petrotrichia) ninakosha, new species; six species within the Petrothrincidae are described as Petrothrincus tsaratananensis, new species, Petrothrincus newidop, new species, Petrothrincus dhritaparam, new species, Petrothrincus pauliani, new species, Petrothrincus andohel, new species, and Petrothrincus andring, new species; and two new species within the Sericostomatidae are described as Cheimacheramus rossi, new species, and Rhoizema mahalevonum, new species. The genus Gyrocarisa Weaver 1997 is synonymized with Petrothrincus Barnard 1934, resulting in the new combinations Petrothrincus steineri (Weaver 1997), new combination, Petrothrincus concava (Weaver 1997), new combination, Petrothrincus acuta (Weaver 1997), new combination, Petrothrincus scottae (Malm & Johanson 2005), new combination, and Petrothrincus weaveri (Malm & Johanson 2005), new combination. A key is presented to males of all Sericostomatoidea species from Madagascar. Distribution maps are given for all new and previously described Madagascar species within the superfamily.